Priming Astrocytes With HIV-Induced Reactive Oxygen Species Enhances Their Trypanosoma cruzi Infection - Urquiza, Javier; Cevallos, Cintia; Elizalde, María Mercedes; Delpino, M. Victoria; Quarleri, Jorge (Frontiers in Microbiology, 2020)
Introduction: Trypanosoma cruzi is an intracellular protozoa and etiological agent that causes Chagas disease. Its presence among the immunocompromised HIV-infected individuals is relevant worldwide because of its impact on the central nervous system (CNS) causing severe meningoencephalitis. The HIV infection of astrocytes – the most abundant cells in the brain, where the parasite can also be hosted – being able to modify reactive oxygen species (ROS) could influence the parasite growth. In such interaction, extracellular vesicles (EVs) shed from trypomastigotes may alter the surrounding environment including its pro-oxidant status. Methods: We evaluated the interplay between both pathogens in human astrocytes and its consequences on the host cell pro-oxidant condition self-propitiated by the parasite – using its EVs – or by HIV infection. For this goal, we challenged cultured human primary astrocytes with both pathogens and the efficiency of infection and multiplication were measured by microscopy and flow cytometry and parasite DNA quantification. Mitochondrial and cellular ROS levels were measured by flow cytometry in the presence or not of scavengers with a concomitant evaluation of the cellular apoptosis level. Results: We observed that increased mitochondrial and cellular ROS production boosted significantly T. cruzi infection and multiplication in astrocytes. Such oxidative condition was promoted by free trypomastigotes-derived EVs as well as by HIV infection. Conclusions: The pathogenesis of the HIV-T. cruzi coinfection in astrocytes leads to an oxidative misbalance as a key mechanism, which exacerbates ROS generation and promotes positive feedback to parasite growth in the CNS.